Perlindungan Hukum Dalam Modernisasi Umkm Melalui Penerapan Fintech Di Era Digital (Studi Kasus Pada Otoritas Jasa Keuangan dan Dinas Koperasi dan UMKM Provinsi Lampung) - Recca Ayu Eka Hapsari; Yulia Eka Hesti; Desnia Kasih Eka Gea (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The rise of developments during the Industrial Revolution 4.0 era of digitalization in the world certainly makes everything the needs of every human being who use it feel more efficient and modern. The benefits and conveniences offered also make every country compete to make the digitalization era a trend. In this study, the author uses research by collecting data by reading legal books, studying books related to the case available in the literature that has to do with this research, besides that the author also uses websites that have a relationship with the problem that the author takes. , so that the data is collected in a concrete and accurate manner and the author also uses an empirical approach that is done by looking at the object being studied and conducting interviews. MSME activities that use financial technology are regulated in OJK Regulation Number 77 of 2016 (POJK) concerning Information Technology-Based Lending and Borrowing Services. In Chapter I article 1 paragraph 3 it is stated that Information Technology-Based Borrowing and Borrowing Services is the provision of financial services to bring together lenders and loan recipients in order to enter into lending and borrowing agreements in rupiah currency directly through an electronic system using the internet network.